Ethical theory of Al-Ghazali - Dudić Mevlud; Smailagić Sumeja (Univerzitetska Misao)
In this article, the author examines the role of moral philosophy and its significance within the philosophical-theological thought of Abu Hamid Muhammad ibn Muhammad al-Ghazali (Arabic: الغزالي محمد بن محمد حامد أبو). Al-Ghazali is regarded as one of the most important figures in the Muslim intellectual tradition, leaving behind a rich body of work. The author demonstrates how ethics plays a central role in Al-Ghazali's philosophy, which evolves into a synthesis of philosophical-theological thought and, in his later years, mystically oriented thinking. Through works such as Ihya Ulum al-Din, Tahafut al-Falasifa, and Al-Munqidh min al-Dalal, Al-Ghazali integrates Sufism with Sharia law, critiques Peripatetic philosophy, and describes his spiritual journey. Al-Ghazali's interpretation of moral issues will have a significant influence on the development of later philosophical-theological thought in Islam, laying the groundwork for the harmonization of Sufism with orthodox Islam and influencing Muslim and European intellectual currents.